Weight and fat distribution in patients taking valproate: A valproate-discordant gender-matched twin and sibling pair study - Petty, S.; Kantor, S.; Lawrence, K.; Berkovic, S.; Collins, M.; Hill, Keith; Makovey, J.; Sambrook, P.; O'Brien, T.; Wark, J. (Wiley-Blackwell Publishing, Inc., 2014)
Objectives: Chronic treatment with valproate (VPA) is commonly associated with weight gain, which potentially has important health implications, in particular increased central fat distribution. We utilized a VPA-discordant same-sex, twin and matched sibling pair study design to primarily examine for differences in fat distribution between patients with epilepsy treated with VPA compared to their matched twin or sibling control. Weight, blood pressure, and leptin levels were assessed. Methods: Height, weight, waist and hip measurements, exercise, blood pressure (BP), and serum leptin levels were measured. Body composition was measured using dual-energy x-ray absorptiometry (DXA). Abdominal fat was expressed as a percentage of the abdominal region (AFat%); and of whole body fat (WBF); (AFat%WBF). Mean within-pair differences were assessed (VPA-user and nonuser). Restricted maximum likelihood (REML) linear mixed model analysis was fitted to examine associations of anthropometrics, zygosity, gender, menopausal status, VPA dose and duration, with weight and AFat%.Results: We studied 19 pairs of VPA-discordant, gender-matched (five male, 14 female) twins and siblings. Mean (standard deviation, SD) duration of therapy for VPA users was 11.0 (7.4) years. There were no statistically significant within-pair differences in age, height, weight, body mass index (BMI), BP, leptin level, WBF, AFat%, or AFat%WBF. For pairs in which VPA-user was treated for >11 years there were statistically significant mean within-pair differences in AFat%, (+7.1%, p = 0.03, n = 10 pairs), mean BP (+11.0 mm Hg, p = 0.006, n = 8 pairs); but not in AFat%WBF. VPA duration was positively associated with weight (estimate +0.98 kg/per year of VPA, p = 0.03); VPA treatment duration and dose were not significantly associated with AFat%. Significance: This study demonstrated a relationship between long-term VPA use and abdominal adiposity (AFat%), which could have significant health implications. We recommend ongoing monitoring of weight, BMI, and blood pressure for patients taking VPA